2021
DOI: 10.1002/anie.202016469
|View full text |Cite
|
Sign up to set email alerts
|

On‐Surface Synthesis of Nitrogen‐Doped Kagome Graphene

Abstract: Nitrogen‐doped Kagome graphene (N‐KG) has been theoretically predicted as a candidate for the emergence of a topological band gap as well as unconventional superconductivity. However, its physical realization still remains very elusive. Here, we report on a substrate‐assisted reaction on Ag(111) for the synthesis of two‐dimensional graphene sheets possessing a long‐range honeycomb Kagome lattice. Low‐temperature scanning tunneling microscopy (STM) and atomic force microscopy (AFM) with a CO‐terminated tip supp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
29
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 38 publications
(30 reference statements)
0
29
0
Order By: Relevance
“…At this stage, the adsorbed superstructure is alterable enough, so that weak metal–monomer bonds can be broken and re-formed to reach thermodynamically stable, defect-free, optimal configuration. In surface-assisted polymerization reactions, the morphology of this optimal metal–organic assembly is then transmitted to the final polymer in which, usually upon heating, coordination bonds are replaced by covalent bonds. , Understanding the ways in which metal–organic precursors are formed prior to the covalent bonding is thus an important task in custom designing and directing polymerization reactions on surfaces.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…At this stage, the adsorbed superstructure is alterable enough, so that weak metal–monomer bonds can be broken and re-formed to reach thermodynamically stable, defect-free, optimal configuration. In surface-assisted polymerization reactions, the morphology of this optimal metal–organic assembly is then transmitted to the final polymer in which, usually upon heating, coordination bonds are replaced by covalent bonds. , Understanding the ways in which metal–organic precursors are formed prior to the covalent bonding is thus an important task in custom designing and directing polymerization reactions on surfaces.…”
Section: Introductionmentioning
confidence: 99%
“…In surface-assisted polymerization reactions, the morphology of this optimal metal−organic assembly is then transmitted to the final polymer in which, usually upon heating, coordination bonds are replaced by covalent bonds. 23,24 Understanding the ways in which metal−organic precursors are formed prior to the covalent bonding is thus an important task in custom designing and directing polymerization reactions on surfaces.…”
Section: Introductionmentioning
confidence: 99%
“…These types of flat bands have been realized in artificial systems based on atomic lattices [127][128][129][130][131]. They can also be formed in suitable engineered, chemically synthesized lattices, where covalent organic frameworks and metal-organic frameworks are especially attractive systems for realizing these artificial models [132][133][134][135][136][137][138][139][140].…”
Section: A Generating Flat Bands From Geometric Frustrationmentioning
confidence: 99%
“…While there are extensive results on the formation of the onedimensional nanocarbons (graphene nanoribbons) [131,[143][144][145][146][147], challenges remain to create two-dimensional assemblies with very high quality [148][149][150]. However, there are recent experimental results that are pushing this field towards higher quality samples towards the formation of flat bands in the MOF or COF band structure [119,140,142,151]. The realized strategies rely on making a molecular network with a kagome lattice with one of the examples highlighted in Fig.…”
Section: B Experiments Flat Bands From Frustrationmentioning
confidence: 99%
“…Although Kagome graphene has not been successfully synthesized yet, Chen et al suggested a self-assembly process (from cyclopropane) on single-layer boron nitride, as the lattice mismatch is only about 2% [7]. Additionally, Pawlak et al [11] recently published a successful synthesis process of nitrogen-doped graphene on an Ag (111) substrate, a 2D material that also has a Kagome pattern [11]. With growing interest in the synthesis of these types of material, it is evident that the actualization of materials with KG-like properties has merit, and understanding the mechanical properties of Kagome lattice structures may prove valuable.…”
Section: Introductionmentioning
confidence: 99%